Water–structure interaction analysis of a segmental bridge using ambient vibration testing at diferent water levels (2023)
ABSTRACT: Updating a fnite-element (FE) model using dynamic parameters obtained from feld testing requires an adequate understanding of the variation of such parameters due to changes in environmental conditions. This paper presents an experimental program to study the infuence of the water–structure interaction in the dynamic response of a prestressed concrete segmental bridge with partially submerged piers in an artifcial reservoir. The bridge, located in Colombia, has a total length of 558 m. Ambient Vibration Tests (AVTs) consisted of four experimental campaigns at diferent water levels to perform modal identifcation. In addition, existing empirical formulations accounted for the efect of the hydrodynamic masses concentrated in the piers. This paper shows that updating FE models from identifed dynamic properties in partially submerged bridges involves percentage reductions in natural frequencies related to the reservoir's water level. Thus, providing a better insight into the incidence of water–structure interaction on partially submerged bridges' dynamic response. Finally, considerations during dynamic characterization tests are discussed.